A Passover Haggadah : go forth and learn - Silber, David; Furst, Rachel, 1978- (Philadelphia : Jewish Publication Society, 2011)
Hebrew and English text with new commentary and essays. Rabbi Silber has given us two books in one: the Haggadah itself, in English and Hebrew, with his seder commentary and a collection of essays that provide close readings of the classic biblical and rabbinic texts that inform Seder-night ritual and narration. Both parts work beautifully together to illuminate the central themes of Passover: peoplehood, Covenant, our relationship to ritual, God's presence in history, and other important issues that resonate with us all. Just as midrash attempts to bridge the gap between ancient text and cont.
Arami oved avi: the core text of the Haggadah -- Gerut, avdut, innuy: the covenantal formula -- Exodus: an individual and collective coming of age -- Elu eser makot: rereading the plagues -- Korban Pesah: the sacrifice that shaped a nation -- Lot and the destruction of Sodom: a prefiguring of Exodus -- Creation themes in the Exodus story -- Hallel at the Seder: a song of redemption.
Text of Haggadah in Hebrew with English translation ; commentary in English.
Includes bibliographical references.
Print version record.
Master record variable field(s) change: 072
Keywords: Haggadah; Haggadot -- Texts; Seder -- Liturgy -- Texts; Judaism -- Liturgy -- Texts; RELIGION / Judaism / General; Electronic books